2019
DOI: 10.24849/j.geot.2019.145.05
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos mecanismos de compactação em misturas entre solo arenoso e altos teores de emulsão asfáltica

Abstract: RESUMO -Este artigo apresenta uma avaliação dos mecanismos de compactação de misturas entre solo arenoso e altos teores de emulsão asfáltica. Para tanto, foram utilizados um solo classificado pelo Sistema Unificado de Classificação dos Solos como SP e uma emulsão asfáltica catiônica de ruptura lenta (RL-1C). As misturas entre solo e emulsão asfáltica foram confeccionadas com teores de emulsão entre 13% e 31%, em peso, e foram submetidas a diferentes condições de compactação, de forma que as informações obtidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
6
Order By: Relevance
“…Preliminary studies on the compaction of mixtures of sandy soils with high asphalt emulsion contents, 13% to 31%, in weight, have already been performed (Lima, 2016;Lima and Dantas Neto, 2019). These studies involved mixtures prepared by adding a low-breaking cationic asphalt emulsion, classified according the Brazilian standardization as RL-1C type (IPR, 2013), to a soil classified as poor graded sand (SP) and consisted of assessing the compaction energy (standard and modified Proctor) and the viscosity of the asphalt binder.…”
Section: Stabilization Of Soils With Asphalt Emulsionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preliminary studies on the compaction of mixtures of sandy soils with high asphalt emulsion contents, 13% to 31%, in weight, have already been performed (Lima, 2016;Lima and Dantas Neto, 2019). These studies involved mixtures prepared by adding a low-breaking cationic asphalt emulsion, classified according the Brazilian standardization as RL-1C type (IPR, 2013), to a soil classified as poor graded sand (SP) and consisted of assessing the compaction energy (standard and modified Proctor) and the viscosity of the asphalt binder.…”
Section: Stabilization Of Soils With Asphalt Emulsionmentioning
confidence: 99%
“…The results of the studies performed with mixtures of sandy soil with high asphalt emulsion contents also revealed that the stiffness of the formed asphalt film exerts a strong influence on the compaction process of emulsionsoil mixtures (Lima, 2016;Lima and Dantas Neto, 2019). The efficiency of the compaction was obtained only in situations where the emulsion viscosity was significantly low, or with increased compaction energy.…”
Section: Stabilization Of Soils With Asphalt Emulsionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os estudos de misturas solo-emulsão em outras áreas da Geotecnia ainda são muito incipientes, destacando-se algumas aplicações para uso na construção de barragens de terra como os trabalhos JACINTHO [5], LIMA [6], PEREIRA [7], LIMA e DANTAS NETO [8], BRITO [9], DANTAS NETO et al [10] e BRITO et al [11].…”
unclassified